ANALISIS KONFLIK BATIN TOKOH DALAM FILM SAMPAI TITIK TERAKHIRMU KARYA EVELYN AFNILIA UNTUK PEMBELAJARAN TEKS DRAMA DI KELAS XI MAN 2 KOTA BENGKULU - Eka Putri, Meissy; Putri Juni Astuti, Dina; Suradi, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explain the inner conflict of the characters in the film "Terakhirmu" by Evely Afnilia and examine its use as teaching material for drama texts in class X Man 2, Bengkulu City. This study uses a descriptive qualitative method with a literary psychology approach. The research data sources are dialogues, monologues, and scenes depicting the inner conflict of the characters in the film "Terakhirmu" by Evely Afnilia. Data collection techniques were carried out through observation, documentation, and recording relevant data. Data analysis was carried out by identifying, classifying, and interpreting the forms of inner conflict experienced by Koko based on the psychological aspects of the storyline.The results show that the main character experiences various forms of inner conflict, such as disappointment, anxiety, hesitation in making decisions, feelings of fear, anxiety, sadness, and the struggle between hope and reality. These conflicts arise from environmental pressures, relationships between characters, and personal problems that influence character development. The researcher shows that the inner conflict in this film has educational value relevant to teaching drama texts, especially in understanding intrinsic elements such as characters, characterization, conflict, and morals. Therefore, this film can be used as teaching material to improve students' ability to analyze and appreciate drama texts in class XI MAN 2, Bengkulu City.